Evaluation of mineral oils and insecticides on the control of BGMV virus (Golden Mosaic) in Chiapas, Mexico. - Becerra, Noé; Fraire, Guillermo; López, Ernesto (Agronomía Mesoamericana, 2016)
Upon evaluating the effect of two mineral oils and two insecticides on the control of the BGMV in three genotypes of black bean, it was found that the variety Negro Tacana given its resistance to the virus, they can or cannot use the products. In Negro Huasteco-81 we could employ this type of products, in order to disminish incidence and increase yield, from 126 kilos with the treatment of Citrolina + Endosulfan; upto 320 kilos with the combined products of Imidacloprid 70 WS and 350 SC and of 281 kilos with Imidacloprid 70 WS. In Negro Cotaxtla-91 can there be are increment of 82 kilos with the treatment of Citrolina + Endosulfan.